Analisis Buku Siswa Matematika Kelas Vii Menurut Taksonomi Timss (Trends in International Mathematics and Science Study) - Ayatina, Nurbaningsih, Prof. Dr.Budi Murtiyasa,M.Kom, Dr. Sabar Narimo,MM,M.Pd (2017)
This study aims to: (1) To describe and analyze the composition of the material in the book Mathematics student of class VII according to TIMSS Taxonomy terms of the content domain (2) To describe and analyze the composition of matter of the book Mathematical student of class VII according to TIMSS Taxonomy terms of the content domain. (3) To describe and analyze the composition of matter of the book Mathematical student of class VII according to TIMSS Taxonomy terms of cognitive domain. This type of research is qualitative research design using the design of the research literature (Lybrary Research) is based on the literatures that have relation with the problem that will be disscused. The results of this study were, (1) It is well known domain book content Numbers with content percentage of 72% later in the Algebra domain book by 17% and geometry content domain material is only 11%. Because the study only focused on the first half (Numbers, Association, Comparison, Lines and Angles) are not included in the domain of Data and Chance the content domain Data and Chance are excluded or included into the issue of the next book in the second half (2) The results of domain konten Math exercise book analyzes known as domain Number reached 69,2% about domain Geometri reached 9,9%. Then for Algebra domain reached 20,9% while for Data and Probability 0%.(3) It`s kown that from 263 of item which analyzed known 43 item reached kognitif degree at domain knowing percentage 16,35%, 161 item reached kognitifdegree,at domain Applying percented 61,22%,while 59 item has reached kognitif degree at domain reasoning percented 22,43% (4) It is known from 263 item analysis,Implemmentkognitif aspect from Applying domain as the most dominant aspect with each percentage 50,31% or 81 item.Meanwhile for measure aspect which belong to domain knowing are not includedin items. Keywords :, content analysis, cognitive analysis, math books